Lost in Translation: Word Sense Disambiguation. - Lian Tze, Lim; Tang, Enya Kong (2004)
In natural languages, a word can take on different meanings in different contexts. Word sense disambiguation (WSD) refers to the task of determining the correct meaning or sense of a word in context.